Detection and quantification of quitinasa in banana (Musa spp.) leaves inoculated with Mycosphaerella fijiensis - Cynthia Sánchez-García; Mileidy Cruz-Martín; Yelenys Alvarado-Capó; Luis Rojas; Michel Leiva-Mora; Mayra Acosta-Suarez; Berkis Roque (Biotecnología Vegetal, 2012)
The knowledge of the role of chitinase enzyme in Musa spp- Mycosphaerella fijiensis interaction is still very limited. Therefore, their study is of great interest, mainly in breeding programs. The aim of this study was to detect and quantify chitinase enzyme in leaves of ‘Grande naine’ and ‘Calcutta 4’ inoculated with M. fijiensis in greenhouse conditions. This enzyme accumulation was detected in leaves of both genotypes and at different times after inoculation using agarose gel with glycol chitin as a substrate and it was revealed by using Calcoflour brightener. It was noted that in ‘Calcutta 4’ plants there was an increase in chitinase activity in inoculated compared to non-inoculated plants at all times studied. In ‘Grande naine’ inoculated plants this difference was only observed at 2 h and at 3 days after inoculation respect to non-inoculated plants. At each time, the highest values of enzyme concentration corresponded to samples of the resistant genotype. It was shown that the accumulation of this enzyme was related to plant response to pathogen inoculation and was higher in inoculated plants of resistant genotype. Keywords: Black Sigatoka, hydrolytic enzymes, plant defence response, PR proteins